Direito agrário, projetos portuários e comunidades quilombolas: uma análise a partir do projeto de construção do “Porto do Maicá" em Santarém - PA - Sousa, Renata Priscila Benevides de (2018)
The invisibility of the quilombola issue favored by the uncommunicative of studies on the participation and influence on brazilian social formation, determines the element to break with the vulnerability of socio-economic and political condition of the quilombo, remaining and contemporary subjects. This paper proposes an analysis of the relationship "agrarian law, Port Projects and traditional communities Quilombolas", based on participant observation of a concrete case study: "the construction of the port maica", and historical specificities, social, legal and political that composes. It is a field study conducted by the Quilombola communities of the municipality of Santarém-Pará, which are affected directly and indirectly by the bulk carrier enterprise, with interviews of community leaders between 2016 and 2017. The dissertation to see the way the communities involved in the agrarian conflict conquer putting their rights and rights and access to justice, their perceptions of the impacts caused by large agribusiness projects. The study demonstrates the existence of a context of vulnerability and strength, that drives the struggle and the construction of identity of the quilombolas de Santarem – PA.